Investigating intermolecular interactions among CO2, water and PEEK-ionene membrane using cryo ToF-SIMS and isotopic labeling - Yao, Jennifer; Dhas, Jeffrey A.; Strange, Lyndi E.; Bara, Jason E.; Ravula, Sudhir; Walter, Eric D.; Chen, Ying; Heldebrant, David J.; Zhu, Zihua (Frontiers in Chemistry, 2025)
Cryogenic time-of-flight secondary ion mass spectrometry (cryo ToF-SIMS) has emerged as a powerful tool for investigating molecular interactions, speciation, and dynamics in materials for CO2 capture. In this study, we apply cryo ToF-SIMS to probe interactions between CO2, water, and PEEK-ionene membranes—a promising material for direct CO2 capture due to its selectivity, durability, and efficiency. Despite this potential, the mechanisms governing CO2 diffusion and the influence of water vapor on CO2 behavior remain unclear. To address this, we loaded PEEK-ionene membranes with 13CO2 and D2O and employed cryo ToF-SIMS to visualize the 3D distribution of CO2 and water within the membrane. While prior studies suggest that 13CO2 is absorbed under ambient conditions, our cryo ToF-SIMS analysis revealed no enhancement of the 13C/12C ratio, suggesting weak CO2-membrane interactions. As a result, CO2 vaporizes even at low temperatures (−140°C) under vacuum conditions. In contrast, D2O displayed a relatively homogeneous distribution in the membrane, suggesting stronger water-membrane interactions via hydrogen bonding (18–20 kJ/mol). Interestingly, CO2 was not detected in D2O-loaded membranes, indicating minimal interference from water vapor on CO2 diffusion. As a comparison, the cryo ToF-SIMS data show that 13CO2 can readily react with a basic Na2CO3 aqueous solution to form NaH13CO3. These findings demonstrate cryo ToF-SIMS as a critical technique for understanding gas-water-membrane interactions, offering insights for membrane functionalization to improve CO2 capture efficiency.